The (pro)renin receptor and soluble (pro)renin receptor in choriocarcinoma. Issue 5 (5th October 2021) - Morosin, Saije K; Delforce, Sarah J; Kahl, Richard G S; Corbisier de Meaultsart, Celine; Lumbers, Eugenie R; Pringle, Kirsty G
Abstract : This study aimed to determine if the (pro)renin receptor (ATP6AP2) changes the cellular profile of choriocarcinomas from cytotrophoblast cells to terminally syncytialised cells and ascertain whether this impacts the invasive potential of choriocarcinoma cells. Additionally, we aimed to confirm that FURIN and/or site 1 protease (MBTPS1) cleave soluble ATP6AP2 (sATP6AP2) in BeWo choriocarcinoma cells and determine whether sATP6AP2 levels reflect the cellular profile of choriocarcinomas. BeWo choriocarcinoma cells were treated with ATP6AP2 siRNA, FURIN siRNA, DEC-RVKR-CMK (to inhibit FURIN activity), or PF 429242 (to inhibit MBTPS1 activity). Cells were also treated with forskolin, to induce syncytialisation, or vehicle and incubated for 48 h before collection of cells and supernatants. Syncytialisation was assessed by measuring hCG secretion (by ELISA) and E-cadherin protein levels (by immunoblot and immunocytochemistry). Cellular invasion was measured using the xCELLigence real-time cell analysis system and secreted sATP6AP2 levels measured by ELISA. Forskolin successfully induced syncytialisation and significantly increased both BeWo choriocarcinoma cell invasion ( P < 0.0001) and sATP6AP2 levels ( P  = 0.02). Treatment with ATP6AP2 siRNA significantly inhibited syncytialisation (decreased hCG secretion ( P  = 0.005), the percent of nuclei in syncytia ( P  = 0.05)), forskolin-induced invasion ( P  = 0.046), and sATP6AP2 levels ( P < 0.0001). FURIN siRNA and DEC-RVKR-CMK significantly decreased sATP6AP2 levels (both P < 0.0001). In conclusion, ATP6AP2 is important for syncytialisation of choriocarcinoma cells and thereby limits choriocarcinoma cell invasion. We postulate that sATP6AP2 could be used as a biomarker measuring the invasive potential of choriocarcinomas. Additionally, we confirmed that FURIN, not MBTPS1, cleaves sATP6AP2 in BeWo cells, but other proteases (inhibited by DEC-RVKR-CMK) may also be involved.